184k views
5 votes
How do you solve (x + 2) (x-3) ?

User Eric Blum
by
6.5k points

1 Answer

6 votes


Solution, \mathrm{Expand}\:\left(x+2\right)\left(x-3\right):\quad x^2-x-6


Steps:


\left(x+2\right)\left(x-3\right)


\mathrm{Apply\:FOIL\:method}:\quad \left(a+b\right)\left(c+d\right)=ac+ad+bc+bd,\\a=x,\:b=2,\:c=x,\:d=-3,\\xx+x\left(-3\right)+2x+2\left(-3\right)


\mathrm{Apply\:minus-plus\:rules},\\+\left(-a\right)=-a,\\xx-3x+2x-2\cdot \:3


\mathrm{Simplify}\:xx-3x+2x-2\cdot \:3,\\\mathrm{Add\:similar\:elements:}\:-3x+2x=-x,\\xx-x-2\cdot \:3,\\\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^(b+c),\\xx=\:x^(1+1)=\:x^2,\\x^2-x-2\cdot \:3,\\\mathrm{Multiply\:the\:numbers:}\:2\cdot \:3=6,\\x^2-x-6


\mathrm{The\:Correct\:Answer\:is\:x^2-x-6}


\mathrm{Hope\:This\:Helps!!!}


\mathrm{-Austint1414}

User Zenorbi
by
5.7k points